Bilingual complexes: the perspective of the Gradient Symbolic Computation framework*. Issue 5 (11th February 2016) - MUYSKEN, PIETER
Abstract : The paper to which this commentary responds (Goldrick, Putnam & Schwarz, 2016 ) represents a big step forward in a field which was showing signs of stasis – the study of the grammatical properties of intra-sentential code-switching or code-mixing – and this for two reasons. First of all, it explicitly links the insights from the grammatical study of code-mixing to the rich array of results from psycholinguistic research in the domain of bilingual language processing, making use of the Gradient Symbolic Computation framework (GSC; Smolensky, Goldrick & Mathis, 2014 ). Second, it provides a set of tools to handle problems in the domain of code-mixing having to do with simultaneous representations in the domain of bilingual complexes.